Criminalization of Cohabitants in Indonesia: An Attempt at a Compromise Between Positive Law and Islamic Law - M. Taufiq; Kudrat Abdillah; Maylissabet; Jamaluddin Shiddiq (P3M dan Jurusan Syariah dan Ekonomi Bisnis Islam STAIN Sultan Abdurrahman Kepulauan Riau, 2026)
The phenomenon of cohabitation in Indonesia is becoming increasingly prevalent, in line with social changes in modern society, which tends to be more open to relationships outside marriage. This situation raises legal issues concerning the boundaries between the private sphere of the individual and the state’s authority to regulate public morality. Under the provisions of the Criminal Code (Law No. 1 of 2023), cohabitation is classified as an offense punishable under certain conditions, thereby sparking debate within society. This study employs a normative legal methodology using both a legislative and a conceptual approach. The data sources consist of primary, secondary, and tertiary legal materials analyzed qualitatively. The issues addressed in this study include how the criminalization of cohabitation is regulated under Indonesian positive law. Furthermore, this study examines the perspective of Islamic law on cohabitation. Another issue is why there is debate regarding the criminalization of cohabitation in Indonesia. The research findings indicate that the criminalization of cohabitation under Indonesian positive law is regulated as a complaint-based offense, limiting law enforcement to specific parties. From an Islamic law perspective, cohabitation is a prohibited act as it falls under the category of zina, which contradicts the principles of Sharia. The debate arises due to a conflict between moral and religious values and the principles of privacy rights and individual freedom within the modern legal system.